2015
DOI: 10.1371/journal.pone.0121215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Restless Legs Syndrome among Chinese Adults in a Rural Community of Shanghai in China

Abstract: AimsThe primary objective of this study was to investigate the prevalence and risk factors of restless legs syndrome (RLS) in an adult Chinese population living in a rural community. We also aimed to determine the predictive diagnostic value of the 4-item screening questionnaire for RLS in this population.MethodsThis study was designed as a 2-phase survey. In phase 1 we performed a face-to-face interview of eligible individuals living in a rural community in Shanghai using a 4-item screening questionnaire. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
(39 reference statements)
3
20
2
1
Order By: Relevance
“…An attempt at a differential diagnosis may exclude RLS mimics and affect epidemiological study results. Our results suggest that a questionnaire with a differential diagnosis demonstrates an equivalent prevalence to that of neurological examinations with differential diagnoses [15][16][17][18], which supports the use of the CH-RLSq in accordance with the 2012 revised IRLSSG criteria. Next, the 2012 revised IRLSSG criteria proposed that a frequency cutoff be used as a specifier for the clinical course and that the symptom severity be used as a specifier for clinical significance.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…An attempt at a differential diagnosis may exclude RLS mimics and affect epidemiological study results. Our results suggest that a questionnaire with a differential diagnosis demonstrates an equivalent prevalence to that of neurological examinations with differential diagnoses [15][16][17][18], which supports the use of the CH-RLSq in accordance with the 2012 revised IRLSSG criteria. Next, the 2012 revised IRLSSG criteria proposed that a frequency cutoff be used as a specifier for the clinical course and that the symptom severity be used as a specifier for clinical significance.…”
Section: Discussionsupporting
confidence: 72%
“…The 8 studies from other Asian countries that included differential diagnosis assessments by a neurological exam or interview also reported a relatively low prevalence, with a range of 0.7-5.2% [15][16][17][18][48][49][50][51]. More than half (6 of 10) of the studies that employed faceto-face or telephone interviews with set-of-symptoms criteria also showed a generally low prevalence (0.1-5.5%) [12-14, 40, 42, 45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 17 Race/ethnicity, sex, and age Few studies have examined the prevalence RLS/WED by race/ethnicity within the same population, and noncomparison reports have suggested that the proportion of people with RLS/WED, especially those experiencing symptoms at least once a month, is higher among white people than in other populations. [12][13][14][15][16][17][18][19][20][21][22] In adults over the age of 35, RLS/WED occurs about twice as often in women as in men. 3 23 However, virtually no sex difference is seen for adults under 35 years old.…”
Section: Clinical Definition Of Rls-wedmentioning
confidence: 99%
“…Interestingly, when compared by gender, hypertension was a risk factor for RLS in males but not in females in this study. 36 Pennestri et al 37 analyzed PLMS subjects with RLS (N=14) and without RLS (N=14). They found a significant increase of the heart rate and systolic and diastolic blood pressure (SBP and DBP) during PLMS in both groups.…”
mentioning
confidence: 99%